Classification of Wheezing Children in Rural Bangladesh by Intensity of Ascaris Infection, Total and Specific IgE Levels, History of Pneumonia, and Other Risk Factors. (5th December 2019) - Takeuchi, Haruko; Khan, Md Alfazal; Zaman, Khalequz; Takanashi, Sayaka; Hasan, S. M. Tafsir; Yunus, Mohammad; Iwata, Tsutomu
Abstract : Ascaris lumbricoides is the most common soil-transmitted helminth and infects 447 million people in impoverished areas worldwide. It causes serious morbidity including wheezing and influences various aspects of human immunity, such as type 2 innate lymphoid cells, regulatory T cell function, and acquired immunity. Thus, it is crucial to elucidate its influence on human immunity. We aimed to classify wheezing children based on their Ascaris infection intensity and other risk factors using hierarchical cluster analysis to determine the mechanisms of and the degree to which Ascaris contributes to childhood wheezing in rural Bangladesh. We analyzed relevant data collected in 2001. The participants included 219 5-year-old wheezing children who were randomly selected from 1705 children living in the Matlab Health and Demographic Surveillance area of the International Centre for Diarrhoeal Disease Research, Bangladesh. Hierarchical cluster analysis was conducted using variables of history of pneumonia, total and specific immunoglobulin E levels, Ascaris infection intensity, and parental asthma. Three distinct wheezing groups were identified. Children in Cluster 1 (n = 50 ) had the highest titers of the total, anti- Ascaris, anti- Dermatophagoides pteronyssinus, and anticockroach IgEs and experienced the fewest episodes of pneumonia. Cluster 2 (n = 114 ), the largest group, experienced few episodes of pneumonia and had the lowest titers of the total, anti- Ascaris, anti-Dp, and anticockroach IgEs. Cluster 3 (n = 32 ) consisted of participants with the most episodes of pneumonia and lower titers of the total and specific IgEs. The extremely high prevalence of Ascaris infection found in Clusters 1-3 was 78%, 77%, and 72%, respectively. Childhood wheezing in rural Bangladesh could be divided into three groups, with 26% of wheezing attributable to anti- Ascaris IgE and 16% to history of pneumonia during early childhood, and 58% might have been due to Ascaris infection without elevated anti- Ascari s IgE.